Perbedaan Hasil Keterampilan Proses Sains Melalui Model Pembelajaran Inquiry dan Model Pembelajaran Inquiry dengan Metode Pictorial Riddle bagi Siswa SMP Negeri 1 Gunungsari Tahun Ajaran 2015/2016 - Yunita Yunita; Muhammad Zulfikar Syuaib; Muhammad Taufik (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2016)
The experimental research is aimed to revealing the difference between science process through inquiry learning model and inquiry learning model with pictorial riddle method for students in SMP Negeri 1 Gunungsari academic year 2015/2016. The research designs is using pretest posttest control group design. The samples were chosen by purposive sampling technique. The population is all students of SMP Negeri 1 Gunungsari grade VIII, while the samples are theÃÂ  students in VIII D class (experiment class 1) and VIII F class (experiment class 2). The instrument of this research ÃÂ is the science process skills test in form of reasoned multiple choice, which has been tested statistically itÃ¢â¬â¢sÃÂ  validity, reliability, discrimination index and level of difficulty of ÃÂ the item. The data analysed used ÃÂ independent sample t-test at significantÃÂ  level ÃÂ of 5 % with ÃÂ tcount is 2,535 and ttable ÃÂ is 1,671 because tcoun > ttable,, then H0 ÃÂ isÃÂ  rejected and Ha accepted. The result indicates that there is a difference between science process through inquiry learning model andÃÂ  inquiry learningÃÂ  model withÃÂ  pictorial riddleÃÂ  method for student in SMP Negeri 1 Gunungsari academic yearÃÂ  2015/2016.ÃÂ